Chemical modification and antioxidant activity of Wendan peel polysaccharide - Bobo Lin; Gangliang Huang (Scientific Reports)
Abstract Wendan peel polysaccharide (PP) was modified using different chemical methods. The acetylation modification of PP using acetic anhydride method resulted in a degree of substitution of 0.42 for acetylated Wendan peel polysaccharide (Ac-PP). The phosphate method was used to phosphorylate PP, and successfully obtained phosphorylated Wendan peel polysaccharide (P-PP) with a degree of substitution of 0.21. The carboxymethylation modification of PP was carried out using isopropanol-chloroacetic acid method, and the degree of substitution of carboxymethylated Wendan peel polysaccharide (CM-PP) obtained after modification was 0.77. In order to further confirm the success of the three modification methods, nuclear magnetic resonance and infrared analysis methods were used to analyze the three derivatives, and it was found that all three derivatives had characteristic absorption peaks and functional groups, indicating that the chemical modification was successful. The antioxidant activity of PP and three chemically modified products were evaluated by measuring their ability to scavenge different free radicals. The experimental results indicated that not all chemical modifications could significantly enhance the antioxidant activity of polysaccharides. In the experiment, when vitamin C (Vc) was used as the control group, the antioxidant capacity of P-PP was more prominent. At a concentration of 3.2 mg/mL, the scavenging rate of P-PP on DPPH free radicals could reach 72.50%, and the scavenging rate on superoxide anions was 69.38%.These results indicated that the antioxidant activity of modified polysaccharides was improved, which might be due to the introduction of new active functional groups through chemical modification, thereby altering the structure of polysaccharides.